18V to 1000V boost converter - Bennedict Bally, Anak Narok (2009)
Recent advances in semiconductor, magnetic and passive technologies make the switching power supply an ever more popular choice in the power conversion arena today. These supplies offer lightweight, smaller footprints and improved efficiencies over traditional power supplies. The objective of this project is to develop a boost converter which can be operated in many ways in order to obtain the desired output. The operation of power supply circuits was built by using microcontroller and pulse width modulator (PWM) which can produce a PWM as an input from the controller for the boost circuit. This project has been divided into two, using PIC16F877A and using pulse modulator, SG3525AN. The boost topology is used in the circuit for arrangement of the power devices and the other elements. The frequency and period of the pulse width has to be determined first in order to get the 1000V output. C Compiler software is used to program the PIC16F877. For SG3525AN, it will generate the pulse by itself to be supply to the boost circuit. As the result, the direct current (DC) 1000V output voltage remains constant through the time. This boost converter can be used for multipurpose and further research need to be done to complete this circuit to the full potential.